If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 2x + 105 Reorder the terms: 6x = 105 + 2x Solving 6x = 105 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6x + -2x = 105 + 2x + -2x Combine like terms: 6x + -2x = 4x 4x = 105 + 2x + -2x Combine like terms: 2x + -2x = 0 4x = 105 + 0 4x = 105 Divide each side by '4'. x = 26.25 Simplifying x = 26.25
| 0.5p+4.1=5.7-0.3p | | F=-2575+35x | | 4x-3=-5x-21 | | 30=2t-17t | | j+2=14 | | 15c=5 | | 2x+105=6x | | N+2n=57 | | -X+3(3)=12 | | -5x+10=-14-x | | 356b+56=-832 | | -17s+13s-8=-12 | | 2y-2y+y=17 | | 3x+1.5=6 | | 54=m(m-3) | | 8j(4k)= | | 15(x)=6+14(x) | | 2(x+2)=-6 | | -832=56b+356 | | 224=(W-8)+W+(W-8)+W | | -2(n-7)=-6 | | 16m-7m=18 | | 128=(W-8)+W+(W-8)+W | | 12q-7q=20 | | 3x^2+10=110+x^2 | | 7x+5=3x+17-3x | | ((cos^2)(x))+2cosx+1=0 | | -8+5b+7=b+5+6 | | 8*1-18= | | -18m+6m-2m=14 | | -2(3n-5)-(3-4n)=-3 | | -X+2(1)=6 |